The Decomposition of Hotel Productivity Change in Taiwan from Overall and Disaggregate Perspectives - Ming-Chung Chang; Chiang-Ping Chen; Kuo-Wei Chou (Tourism and Hospitality)
It is necessary for the allocation of resources to be more efficient, and making more adequate operational strategies to realize productivity change is contributed to by the kind of output sources in the hotel’s production process. This study tries to propose hotel productivity change models from overall and disaggregate perspectives by using the Luenberger productivity index based on directional distance function. Empirical findings briefly show that the overall productivity change of ITHs in Taiwan has a growing trend and is driven from a technical change rather than an efficiency change. Moreover, the disaggregate hotel productivity growth comes from the service of hotel facilities, but improving the performance of the catering service is more important to a hotel’s overall performance. Individual ITHs can grasp the contribution of disaggregate hotel productivity growth on the overall productivity change, maintaining or developing competitive advantages in the hotel’s operation and management. Therefore, the viewpoint of this study can not only be used to examine the hotel issues but also be applied to other issues in the hospitality and tourism industry that target overall and disaggregate productivity growth.